2007
DOI: 10.1096/fj.06-7719com
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cardiac protection from ischemia/reperfusion injury: a role for caveolae and caveolin‐1

Abstract: Caveolae, small invaginations in the plasma membrane, contain caveolins (Cav) that scaffold signaling molecules including the tyrosine kinase Src. We tested the hypothesis that cardiac protection involves a caveolin-dependent mechanism. We used in vitro and in vivo models of ischemia-reperfusion injury, electron microscopy (EM), transgenic mice, and biochemical assays to address this hypothesis. We found that Cav-1 mRNA and protein were expressed in mouse adult cardiac myocytes (ACM). The volatile anesthetic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
149
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(164 citation statements)
references
References 51 publications
12
149
2
1
Order By: Relevance
“…Concentrations of isoflurane (0.7%, 1.4%, and 2.8% vol/vol in air) were chosen based on the minimum alveolar concentrations (MAC) in rodents (where 1.4% vol/vol is equivalent to 1 MAC [24]). We have previously confirmed that 1.4% vol/vol isoflurane produces 0.165 ± 0.003 mM isoflurane in media in our metabolic chamber [15]. Cell death was quantified by counting trypan blue-stained cells with results expressed as a percentage of total cells counted ( Figure 1).…”
Section: Simulated Ischemia/reperfusion (Si/r) In Isolated CMsupporting
confidence: 72%
See 2 more Smart Citations
“…Concentrations of isoflurane (0.7%, 1.4%, and 2.8% vol/vol in air) were chosen based on the minimum alveolar concentrations (MAC) in rodents (where 1.4% vol/vol is equivalent to 1 MAC [24]). We have previously confirmed that 1.4% vol/vol isoflurane produces 0.165 ± 0.003 mM isoflurane in media in our metabolic chamber [15]. Cell death was quantified by counting trypan blue-stained cells with results expressed as a percentage of total cells counted ( Figure 1).…”
Section: Simulated Ischemia/reperfusion (Si/r) In Isolated CMsupporting
confidence: 72%
“…We have recently shown that isoflurane increases the recruitment and phosphorylation of Src kinase and caveolin-1 into myocardial caveolar fractions. We have also shown that this phosphorylation of Src and caveolin-1 are required for isoflurane-induced cardiac protection [15]; isoflurane increased the phosphorylation of caveolin-1 in a Src-dependent manner and caveolin-1 knockout mice were not able to be protected from myocardial ischemia/reperfusion injury by isoflurane. Importantly, myocytes isolated from these animals have normal caveolae (unpublished observations).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Caveolin-1 deficiency was also seen in rat models of PH (22,23), and the cell-permeable Cav1 inhibitory peptide prevented the development of monocrotaline-induced PH (24). In addition, decreased expression of caveolin-1, predominantly in endothelial cells, was observed in lungs of patients with severe idiopathic pulmonary arterial hypertension (IPAH) (23,25). In the present study, we addressed the potentially important mechanism of pulmonary vascular remodeling and PH associated with caveolin-1 deficiency.…”
Section: Introductionmentioning
confidence: 97%
“…It has been demonstrated that isoflurane specifically interacts with caveolin, a protein-sequestered area in such regions of myocardial membrane (caveolae). 12 Will the anesthetic delivery by lipid infusion alter how the anesthetic partitions into such specific regions of membrane? Might the enhanced protection at apparently low anesthetic concentrations be due, in part, to the delivery or the alterations to specific regions of the cell membranes and organelles?…”
mentioning
confidence: 99%